Pets as Sentinels, Forecasters and Promoters of Human Health 2019
DOI: 10.1007/978-3-030-30734-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Pets as Sentinels of Human Exposure to Neurotoxic Metals

Abstract: The idea that animals may be used as sentinels of environmental hazards pending over humans and the associated public health implications is not a new one. Nowadays pets are being used as bioindicators for the effects of environmental contaminants in human populations. This is of paramount importance due to the large increase in the worldwide distribution of synthetic chemicals, particularly in the built environment. Companion animals share the habitat with humans being simultaneously exposed to and suffering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…This is reasonable because CUPs and PCMs are oen used for pet hygiene and may come into direct contact with pet hair during their applications, whereas PAHs and OPEs are released into the indoor environment from other sources (such as cooking and furniture) and then mainly partitioned to pet hair via air and dust or other routes. 11 PCMs are commonly found in personal care products, such as shampoos, lotions, detergents, and pet toiletries, 29 and Table 1 Range, mean and median concentrations of individual polycyclic aromatic hydrocarbons (PAHs), organophosphate esters (OPEs), polycyclic musks (PCMs), antibiotics and current-use pesticides (CUPs) in indoor dust (ng g −1 dw), pet hair (ng g −1 dw) and indoor air (ng m −3 ) CUPs are used for control of pests and fungi. The applications of shampoos and detergents for pet bath and pest control sprays might lead to high concentrations of PCM and CUP residues in pet hair.…”
Section: Chemical Occurrence In Air Dust and Hairmentioning
confidence: 99%
See 2 more Smart Citations
“…This is reasonable because CUPs and PCMs are oen used for pet hygiene and may come into direct contact with pet hair during their applications, whereas PAHs and OPEs are released into the indoor environment from other sources (such as cooking and furniture) and then mainly partitioned to pet hair via air and dust or other routes. 11 PCMs are commonly found in personal care products, such as shampoos, lotions, detergents, and pet toiletries, 29 and Table 1 Range, mean and median concentrations of individual polycyclic aromatic hydrocarbons (PAHs), organophosphate esters (OPEs), polycyclic musks (PCMs), antibiotics and current-use pesticides (CUPs) in indoor dust (ng g −1 dw), pet hair (ng g −1 dw) and indoor air (ng m −3 ) CUPs are used for control of pests and fungi. The applications of shampoos and detergents for pet bath and pest control sprays might lead to high concentrations of PCM and CUP residues in pet hair.…”
Section: Chemical Occurrence In Air Dust and Hairmentioning
confidence: 99%
“…This concern is intensied with the increasing population of pet owners in recent years 10 and pets have been proposed to be sentinels of indoor contamination. 11,12 Although several studies showed that some contaminants could accumulate in pet hair, the health risk from pet hair exposure is largely unknown. Limited information is available so far on the occurrence of diverse classes of contaminants in pet hair, in comparison to other indoor environmental media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of these systems into pet health care may provide a better understanding of factors that affect pets’ health and pet owners’ benefits. Moreover, data on changes in a pet’s health can be used as pet owner health indicators [ 91 ] and environmental quality indicators [ 92 ].…”
Section: The Five Dimensions: the Essential Fabric Of Interconnectionmentioning
confidence: 99%
“…The life cycle of animals is shorter than in humans. Its monitoring contributes to the early detection of chronic diseases and other health problems resulting from exposure to unhealthy environments ( 90 , 91 ). As favelas' boundaries are not hermetic and do not entirely restrict their contextual effects, improving their health reflects outside them.…”
Section: One Healthmentioning
confidence: 99%